Causal Factors of the Locality Disappearance of Kelayan’s Riverside Settlement in Banjarmasin - Yuniar, Annisa (University of Merdeka Malang, 2020)
Banjarmasin is the capital city of South Borneo province which known as city of one thousand rivers. But nowadays the expansion of riverside localities of Banjarmasin are uncontrolled and almost all of the areas are slums. Slum areas riverside commonly formed by many unorganized building that exceed the river’s borderline and the riverside localities’ behaviors such as throwing the garbage and taking a bath at the river. Our government now focused on handling program to overcome the expansion of riverside slum areas by 100-0-100 movement which means 100% for the water service, 0% for slum area expansion and 100% for sanitation accessibility. Data analysis was descriptive qualitative method with case study approach. Data were collected with observation, questionnaire and interview. Sampling technique was simple random sampling for sample in research location. Result shows that the dominant factors of slum areas at Kelayan riverside are unorganized buildings, uncontrolled garbage and waste management.DOI: https://doi.org/10.26905/lw.v12i2.4166